Prediction of Shaft Resistance of Large Diameter Bored Piles Socketed in Guadalupe Tuff Formation - Seso, Christian G. (Philippine Engineering Journal; Vol 45 No 02 (2024), 2024)
Abstract – In this study, data analytics was utilized to gain insights into the geotechnical engineering properties of the Guadalupe Tuff Formation (GTF). The data came from both the in-situ and laboratory test results of 392 intact rock core samples extracted from the upper layer of the rock mass (0 ~ 30m). By organizing, processing, and analyzing the data, the descriptive statistics of the uniaxial compressive strength (q u (kPa): m = 3,876, median = 3,496, Q1 = 2,500, Q2 = 5,115), Rock Quality Designation (RQD (%): m = 74, median = 75, Q1 = 60, Q2 = 90), dry unit weight ( g (kN/m 3 ): m = 16.8, median = 16.7, Q1 = 16.1, Q2 = 17.4), and elastic modulus of intact rock mass (Ei (kPa): m = 7,497, median = 7,500, Q1 = 5,000, Q2 = 10,000) of the GTF were determined. The shaft resistance of 38 large-diameter bored piles (2.0m–3.0m) was predicted using empirical, analytical, and theoretical methods and compared to mobilized unit shaft resistance determined by high-strain dynamic testing (ASTM D4945). Results suggest that the theoretical method underestimates unit shaft resistance in large-diameter piles socketed in the GTF. Similarly, while the analytical method provides closer predictions of ultimate shaft resistance, it also underpredicts actual values. To achieve economical pile design, developing an empirical method specific to the GTF is recommended. This can be achieved by creating a comprehensive database of load test results of large-diameter bored pile socketed in GTF.   Keywords : rapid thermal annealing, electrophoretic deposition, high-temperature superconductors, supporting electrolytes, superconducting films